Combined sleeve lobectomy for centrally located primary lung cancer and lung cancer with hilar lymph node metastasis. (25th March 2020) - Tsukioka, Takuma; Izumi, Nobuhiro; Komatsu, Hiroaki; Inoue, Hidetoshi; Miyamoto, Hikaru; Ito, Ryuichi; Kimura, Takuya; Nishiyama, Noritoshi
Abstract: Background: Centrally located lung cancer or metastatic hilar lymph nodes can invade the airway and other hilar structures, and they must be removed to achieve complete resection. Methods: We retrospectively assessed the clinical course of 47 patients with centrally located lung cancer or metastatic hilar lymph nodes who underwent sleeve lobectomy from January 2010 to December 2017. Results: The invaded structure other than the airway was the pulmonary artery in 21 patients, chest wall in 3, esophageal muscular wall in 2, vagus nerve in 2, pericardium in 2, left atrium in 1, phrenic nerve in 1 and superior vena cava in 1. Twenty-four patients were treated with sleeve lobectomy alone (simple sleeve lobectomy), and 23 patients were treated with sleeve lobectomy with additional methods (combined sleeve lobectomy). Adverse events occurred in 10 patients (48%) in the simple sleeve lobectomy group and 7 patients (30%) in the combined sleeve lobectomy group. During the follow-up period, 15 patients developed recurrent disease and 12 patients died. Patients in the combined sleeve lobectomy group had significantly shorter overall survival ( P = 0.004) and disease-free survival periods ( P = 0.013). Combined sleeve lobectomy was a significantly poor prognostic factor in the univariate and multivariate analyses. Patients who underwent sleeve lobectomy with an additional method other than angioplasty had a significantly poorer prognosis. However, no patient developed recurrent disease in the hilar area. Conclusions: Combined sleeve lobectomy has acceptable adverse events and good local controllability. However, combined sleeve lobectomy is associated with a significantly poorer prognosis than simple sleeve lobectomy in terms of overall survival and disease-free survival. Abstract : Bronchial sleeve lobectomy with additional methods is feasible for lung cancer treatment.